Exploring Ethnomathematics on The Batik Patterns of Jember In Mathematics Concept - Rizqoh, Zidna; Anas, Aswar; Putra, Eric Dwi (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2024)
This study aims to identify and describe mathematical concepts and describe the results of ethnomathematics exploration contained in Jember batik motifs. The type of research used in this study is qualitative research with an ethnographic approach. The research instruments used were observation, tests, and interviews with batik artisans. The results of this study indicate that the combination of coffee bean and tobacco leaf motifs has applied mathematical concepts of geometry. In the motif of coffee beans and tobacco leaves from the Nhora Pangetu hand-written batik production house, there are mathematical concepts of curves, points, circles, and the concept of dilation. The motif of coffee beans and tobacco leaves from the Gangsar Ngaidin batik production house contains mathematical concepts of reflection (mirroring), congruence, and flat shapes of circles, triangles, and rhombuses.